Salivary alkaline phosphatase and calcium in caries-active type II diabetes mellitus patients: An in vivostudy - Mithra N Hegde; Divya Tahiliani; Shilpa Shetty; Darshana Devadiga (Wolters Kluwer Medknow Publications, 2014)
Background: Diabetes Mellitus is a metabolic syndrome, affecting the oral health in various ways with dental caries being one of the most common problems encountered. Saliva is one of the most abundant secretions in the human body with a variety of natural protective and defence molecules bathing the oral cavity maintaining equilibrium. Its collection is easy and non-invasive. Aims: To compare and evaluate salivary alkaline phosphatase levels and calcium ion levels between caries active type II diabetes mellitus patients and non-diabetics. Materials and Methods: This study was carried out on caries-active age and gender matched 60 non-diabetic and 60 patients with known Type II diabetes mellitus subjects of age group 25-50 years with DMFT index >10. Saliva sample was collected to analyse for alkaline phosphatase enzyme and concentration of calcium ions using Agappe kits. Statistical Analysis: Student 't' test was used to correlate the salivary electrolyte concentration in non- diabetic and diabetic patients with dental caries. A 'P' value of 0.05 or less was considered significant. Results are presented as mean ± standard deviation (X ± SD). Results: The alkaline phosphatase (ALP) activity in saliva was higher in diabetic patients when compared to that of non-diabetic patients with salivary calcium ions were significantly higher in non-diabetic individuals. Conclusion: Diabetes Mellitus patients are more prone to dental caries, hence require intervention to improve the quality of saliva.